Dienophilic reactivity of 2-phosphaindolizines: a conceptual DFT investigation - Beig, Nosheen; Peswani, Aarti; Bansal, Raj Kumar (Beilstein Journal of Organic Chemistry, 2022)
The >C=P– or –N=P– functionality in 1,3-azaphospholo[1,5-a]pyridine, named as 2-phosphaindolizine and its 1- and 3-aza derivatives act as dienophiles and undergo Diels–Alder reactions with 1,3-dienes. However, the dienophilic reactivity is affected by the nature of the substituent groups on the two sides of the σ2,λ3-P atom and also by the presence of more nitrogen atom(s) in the five-membered ring. The conceptual density functional theory (DFT) calculations have been used in recent years to predict the reactivity of organic molecules in reactions. We calculated global hardness (η), global softness (S), electronic chemical potential (μ), electrophilicity (ω), and nucleophilicity (N) indices of four classes of 2-phosphaindolizines, on the basis of which their observed relative dienophilic reactivities could be rationalized. Besides, the Fukui functions of the carbon/nitrogen and phosphorus atoms of the >C=P– and –N=P– functionalities were also computed which revealed their hard electrophilic character and accorded well with the dienophilic reactivities observed experimentally. Furthermore, energies and symmetries of the lowest unoccupied molecular orbitals (LUMO) of 2-phosphaindolizines were found to be in conformity with their dienophilic reactivities.
Keywords: dienophilic reactivity; electronic chemical potential; electrophilicity index; Fukui function; global hardness; nucleophilicity index; 2-phosphaindolizines

(untitled) - Bansal, R. K.; Karaghiosoff, K.; Gupta, N.; Schmidpeter, A.; Spindler, C. (Chem. Ber., 1991)

(untitled) - Karaghiosoff, K.; Bansal, R. K.; Gupta, N. (Z. Naturforsch., B: J. Chem. Sci., 1992)

(untitled) - Bansal, R. K.; Pandey, G.; Gupta, R.; Karaghiosoff, K.; Schmidpeter, A. (Synthesis, 1995)

(untitled) - Bansal, R. K.; Gandhi, N.; Schmidpeter, A.; Karaghiosoff, K. (Z. Naturforsch., B: J. Chem. Sci., 1995)

(untitled) - Bansal, R. K.; Surana, A.; Gupta, N. (Tetrahedron Lett., 1999)

Multiple Bonds and Low Coordination in Phosphorus Chemistry - Appel, R. (Thieme, 1990)

(untitled) - Bansal, R. K.; Gupta, N.; Gupta, N. (Heteroat. Chem., 2004)

Multiple Bonds and Low Coordination in Phosphorus Chemistry - Maerkl, G. (Thieme, 1990)

Phosphorus–Carbon Heterocyclic Chemistry - Maerkl, G.; Kreitmeier, P. (Six-membered Rings with Two or More Heteroatoms with at least One Phosphorus Atom)

(untitled) - Bansal, R. K.; Kumawat, S. K. (Tetrahedron, 2008)

(untitled) - Bansal, R. K.; Jain, V. K.; Gupta, N.; Gupta, N.; Hemrajani, L.; Baweja, M.; Jones, P. G. (Tetrahedron, 2002)

(untitled) - Bansal, R. K.; Gupta, N.; Kumawat, S. K.; Dixit, G. (Tetrahedron, 2008)

(untitled) - Jangid, R. K.; Sogani, N.; Gupta, N.; Bansal, R. K.; Hopffgarten, M. v.; Frenking, G. (Beilstein J. Org. Chem., 2013)

(untitled) - Bansal, R. K.; Karaghiosoff, K.; Gupta, N.; Gandhi, N.; Kumawat, S. K. (Tetrahedron, 2005)

(untitled) - Bansal, R. K.; Gupta, N.; Dixit, G.; Kumawat, S. K. (J. Phys. Org. Chem., 2009)

(untitled) - Hohenberg, P.; Kohn, W. (Phys. Rev., 1964)

(untitled) - Kohn, W.; Sham, L. J. (Phys. Rev., 1965)

(untitled) - Parr, R. G.; Yang, W. (Annu. Rev. Phys. Chem., 1995)

(untitled) - Mendez, F.; Gazquez, J. L. (J. Am. Chem. Soc., 1994)

(untitled) - Yang, W.; Mortier, W. J. (J. Am. Chem. Soc., 1986)

(untitled) - Hirshfeld, F. L. (Theor. Chim. Acta, 1977)

(untitled) - Oláh, J.; Van Alsenoy, C.; Sannigrahi, A. B. (J. Phys. Chem. A, 2002)

(untitled) - Job, G.; Herrmann, F. (Eur. J. Phys., 2006)

Theoretical and Computational Chemistry - Pérez, P.; Domingo, L. R.; Aizman, A.; Contreras, R. (The Electrophilicity Index In Organic Chemistry, 2007)

(untitled) - Domingo, L. R.; Chamorro, E.; Pérez, P. (J. Org. Chem., 2008)

(untitled) - Domingo, L. R.; Pérez, P. (Org. Biomol. Chem., 2011)

(untitled) - Domingo, L. R.; Ríos-Gutiérrez, M.; Pérez, P. (Molecules, 2016)

Frontier Orbitals and Organic Chemical Reactions - Fleming, I. (John Wiley & Sons, 1976)

Gaussian 16, Revision C.01 (Gaussian, Inc., 2016)

(untitled) - Becke, A. D. (J. Chem. Phys., 1993)

(untitled) - Lee, C.; Yang, W.; Parr, R. G. (Phys. Rev. B, 1988)

(untitled) - Baruah, B.; Deuri, S.; Phukan, P. (Comput. Theor. Chem., 2014)

(untitled) - Cerda-Monje, A.; Ormazábal-Toledo, R.; Cárdenas, C.; Fuentealba, P.; Contreras, R. (J. Phys. Chem. B, 2014)

(untitled) - Melin, J.; Aparicio, F.; Subramanian, V.; Galván, M.; Chattaraj, P. K. (J. Phys. Chem. A, 2004)

(untitled) - Melin, J.; Ayers, P. W.; Ortiz, J. V. (J. Phys. Chem. A, 2007)